Integrating assessments of secure tenure rights and co-management for small-scale fisheries in seafood sustainability ratings systems: two new scoring methods for FishSource's sustainability assessments - Govan, Hugh; Alonso-Población, Enrique; Segurado, Susana; Labraña-Cornejo, Rolando; Ferreiro-Velasco, Pedro; Andreu-Cazenave, Miguel (Frontiers in Sustainable Food Systems, 2024)
Market-based approaches to seafood sustainability have gained popularity in the last decade. Marketbased tools, such as certification and ratings systems, enable seafood companies along supply chains to engage in sustainability initiatives while reducing business risks. Yet, these approaches are predominantly utilized in Global North markets and often evaluate performance against standards that build upon resource-intensive, mainstream fisheries management models. These management models have yielded successful outcomes in industrial fisheries, mainly in the Global North, where science, management, and compliance authorities are well resourced. In contrast, artisanal and small-scale fisheries in the Global South have seen limited success in applying mainstream management approaches. Co-management approaches based on secure tenure rights, which emphasize effective partnerships between management authorities and resource users with specific rights over the resources, have shown better outcomes in these contexts. Despite this, market-based tools have largely overlooked co-management principles and tenure rights in their standards. To address this gap, this paper introduces two step-wise evaluative methods designed for the ratings system FishSource, aiming to score whether fishers enjoy secure tenure rights and effectively participate in decision making. The proposed methods use available secondary data to evaluate these crucial aspects of well-managed and equitable small-scale fisheries, while aligning with international policy instruments like the Food and Agriculture Organization Voluntary Guidelines for Securing Sustainable Small-Scale Fisheries and the United Nations Sustainable Development Goals.